2014
DOI: 10.1128/jcm.00051-14
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Evolution of Salmonella enterica Serovar Enteritidis Strains with Different Phage Types

Abstract: c Phage typing has been used for the epidemiological surveillance of Salmonella enterica serovar Enteritidis for over 2 decades. However, knowledge of the genetic and evolutionary relationships between phage types is very limited, making differences difficult to interpret. Here, single nucleotide polymorphisms (SNPs) identified from whole-genome comparisons were used to determine the relationships between some S. Enteritidis phage types (PTs) commonly associated with food-borne outbreaks in the United States. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…Over the last few decades the Colindale phage typing (PT) scheme has played a central role in epidemiological studies of S. Enteritidis while there are limitations regarding Pulsed-field Gel Electrophoresis (PFGE) and Multilocus Variable-Number Tandem Repeat Analysis (MLVA) methods and "neither PFGE nor MLVA could distinguish all of the S. Enteritidis PT30 from various sources, " for example (3)(4)(5). Recent phylogenetic studies based on whole genome sequencing (WGS) have revealed the presence of two separate clonal lineages of S. Enteritidis (6,7). Phage types that dominated in western Europe and Asia, including PT1, PT4, and PT21 occurred in clonal lineage I, while PTs that were most common in North America (i.e., PT8, PT13a, and PT13) comprised the majority of clonal lineage II (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few decades the Colindale phage typing (PT) scheme has played a central role in epidemiological studies of S. Enteritidis while there are limitations regarding Pulsed-field Gel Electrophoresis (PFGE) and Multilocus Variable-Number Tandem Repeat Analysis (MLVA) methods and "neither PFGE nor MLVA could distinguish all of the S. Enteritidis PT30 from various sources, " for example (3)(4)(5). Recent phylogenetic studies based on whole genome sequencing (WGS) have revealed the presence of two separate clonal lineages of S. Enteritidis (6,7). Phage types that dominated in western Europe and Asia, including PT1, PT4, and PT21 occurred in clonal lineage I, while PTs that were most common in North America (i.e., PT8, PT13a, and PT13) comprised the majority of clonal lineage II (6).…”
Section: Introductionmentioning
confidence: 99%
“…Recent phylogenetic studies based on whole genome sequencing (WGS) have revealed the presence of two separate clonal lineages of S. Enteritidis (6,7). Phage types that dominated in western Europe and Asia, including PT1, PT4, and PT21 occurred in clonal lineage I, while PTs that were most common in North America (i.e., PT8, PT13a, and PT13) comprised the majority of clonal lineage II (6).…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella enterica serovar Enteritidis (SE) is a long-standing public health concern in the US (1); salmonellosis can result in hospitalization or death of infants, the elderly, and those with compromised immune systems (2, 3). This pathogen has been strongly associated with poultry farms, eggs, and egg products (4, 5).…”
Section: Introductionmentioning
confidence: 99%
“…Whole genome sequencing (WGS) methods have identified variations across otherwise indistinguishable isolates from eggs and egg products (6, 12), SE associated with reptile feeder mice (13), S. Montevideo from red and black pepper (14). Genome-wide single nucleotide polymorphisms (SNPs) detected by WGS are considered as the most valuable genetic markers for investigating the evolutionary relationships among SE homogeneous isolates (1, 7, 15). Application of WGS have also been useful in other microorganisms, including E. coli (16), Vibrio cholera (17), and Staphylococcus aureus (18).…”
Section: Introductionmentioning
confidence: 99%
“…Given the signatures offered by the polymorphism of the 2 CRISPR loci in our study and in previous works ( 8 , 9 , 13 ), we are convinced that CRISPR DNA targets might be very helpful for subtyping Salmonella , including serotype Enteritidis. Furthermore, because the CRISPR spacer content can be extracted easily from short-read DNA sequences, in contrast to MLVA loci, it could be used to define particular Salmonella Enteritidis strains together with, or as an alternative to, core genome single nucleotide polymorphisms when whole-genome sequencing for foodborne pathogen surveillance and investigation are implemented in public health and veterinary laboratories ( 14 ).…”
Section: Discussionmentioning
confidence: 99%